Ces corps qui comptent : de la matérialité et des limites discursives du sexe - Butler, Judith (Éditions Amsterdam, 2009)
Traduction de Bodies That Matter, (1993) La prise en compte de la matérialité des corps n’implique pas la saisie d’une réalité pure, naturelle, derrière le genre : si le sexe est un présupposé nécessaire du genre, nous n’aurons jamais accès au réel du sexe qu’à travers nos schèmes culturels. Le sexe, comme le genre, est une norme culturelle, qui régit la matérialité des corps. Il importe donc de souligner que le concept de matière a une histoire, où sont sédimentés les discours sur la différence sexuelle. En outre, si certains corps (par exemple blancs, mâles et hétérosexuels) sont valorisés par la norme, d’autres (par exemple lesbiens ou non blancs) sont produits comme abjects, rejetés dans un dehors invivable. À travers une reprise critique du concept foucaldien de « contrainte productive », Judith Butler s’efforce, loin de tout volontarisme, de ressaisir la façon dont ces corps peuvent défaire les normes qui les constituent et devenir le lieu d’une puissance d’agir transformatrice. Ce livre, où l’épistémologie se mêle à la politique, constitue un jalon des études de genre et l’un des ouvrages majeurs de son auteure.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; art contemporain; corps; culture; discipline; fem1000; genre; hétéronormativité; identités LGBTQIA2+; maternité; philosophie; politique; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe; thématiques; épistémologie; épistémologie féministe; épistémologie queer; états-unis; études culturelles

Transformative conversations about sexualities pedagogy and the experience of sexual knowing - Trimble, Lisa (Sex Education : Sexuality, Society and Learning, 2009)
One of the hallmarks of sex education traditionally has been its Cartesian endorsement of mind/body dualism; we have preferred to equate ‘self’ as synonymous with ‘mind’, and have invested heavily in believing in the valence of rationality‐based sexualities education. We generally do not consider the way ‘self’ negotiates, interprets and relates to sexual knowledge in all of our complexity, including our messy, embodied and emotional lives. In this paper I address what I think are several much‐needed conversations for a holistic pedagogy of sexualities to incorporate, including the falseness of the mind/body split, reconsidering what counts as sexual knowledge, the role of the performative in communicating our sexual knowing, and the importance of considering affect in learning about sexualities. The second part of the paper examines pedagogical considerations currently absent in dialogues of sexualities education, such as incorporating transformational learning strategies in teaching sexualities, and what it means to educate toward being a sexual citizen. Finally, I will outline how discussions of epistephenomenology (our relationship to and how we experience knowledge) can contribute to moving toward a vision of a critical, cultural sexualities education.
Keywords: approches et analyses; corps; discipline; discours dominant; phénoménologie; ressource en ligne; savoir expérientiel; science de l'éducation; sciences humaines; sexualité; systèmes d'oppression; thématiques; éducation sexuelle; émotions; épistémologie

Voiles racialisés : la femme musulmane dans les imaginaires occidentaux - Al-Saji, Alia (Les ateliers de l'éthique, 2008)
Cet article étudie deux contextes français dans lesquels les voiles musulmans sont devenus hypervisibles : le débat public qui a mené à la loi française de 2004 interdisant les signes religieux ostensibles dans les écoles publiques, et le projet colonial français de dévoiler les femmes algériennes. Je montre comment le concept de « l’oppression de genre » s’est naturalisé au voile musulman d’une telle manière qu’il justifie les normes de féminités occidentales et cache le mécanisme par lequel les femmes musulmanes sont racialisées. C’est ainsi que le voile devient le point de mire d’un racisme culturel qui se présente comme libérant les femmes musulmanes, un racisme qui semble poser un dilemme au féminisme
Keywords: approches et analyses; corps; discipline; droits des femmes*; europe; fem3400; femmes musulmanes; france; histoire et politique; philosophie; premier cycle; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppression; thématiques

Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000-2009; amériques; discipline; image corporelle; jeunes femmes; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions. https://www.saranahmed.com/
Keywords: 2000-2009; 2000-2029; approches et analyses; corps; discipline; fem1000; féminisme décolonial; identités LGBTQIA2+; identités sexuelles; incontournable; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; thématiques; violences; études culturelles

Queering the Binaries: Transsituated Identities, Bodies, and Sexualities - Cromwell, Jason (The transgender studies reader, 2006)
Keywords: 1900-1999; approches et analyses; corps; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques; trans; états-unis

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Les cinq chansons francophones en tête des palmarès radio et de ventes québécois pour la période comprise entre 1960 et 1990 ont en très forte majorité pour thème central l'amour. Or, comme le souligne Geneviève Sellier à propos du cinéma,"le privilège accordé aux"histoires d'amour" rend nécessaire l'utilisation des théorisations concernant les rapports sociaux de sexe" 1. Ainsi, étudier à la lumière de la notion de genre les paroles des chansons les plus consommées annuellement s'impose. Cette analyse est d'autant plus nécessaire que ces trois décennies ont été marquées par la libération sexuelle et les mouvements féministes, éléments annonciateurs de bouleversements des identités sexuées. Nous tenterons d'évaluer comment, à travers le thème des rapports amoureux, la chanson populaire francophone consommée au Québec représente les identités sexuées entre 1960 et 1990. Nous constaterons que le thème des rapports amoureux s'est fortement modifié au cours de la période. On assiste au déclin du"mythe du Prince Charmant". Toutefois, l'hétéronormativité, loin d'être remise en question dans les chansons, tend à être accentuée au cours de la période. Si au niveau des rapports amoureux, la chanson populaire reflète certains bouleversements en cours dans la société québécoise, elle est loin de remettre en question les catégories homme-femme. L'érosion du mythe de l'amour n'a pas permis de mettre fin à la bicatégorisation dans la chanson, malgré une plus grande souplesse des représentations des identités sexuées. 1 Geneviève Sellier,"Une histoire du cinéman avec les femmes est-elle possible?", dans Anne-Marie Sohn et Françoise Thélamon dir., L'histoire sans les femmes est-elle possible ?, [S. I.] Perrin, 1998, p. 143.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amour; amériques; analyse de discours; approches et analyses; corps; culture populaire; discipline; histoire; hétérosexisme; mémoires/thèses; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sofia; stéréotypes de genre; systèmes d'oppression; thématiques

Precarious life: The powers of mourning and violence - Butler, Judith (Verso, 2004)
Responding to the US’s perpetual war, Butler explores how mourning could inspire solidarity.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; guerre; histoire et politique; médias; philosophie; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; violences; états-unis; éthique

Unbearable weight: Feminism, western culture, and the body - Bordo, Susan (University of California Press, 2003)
Susan Bordo untangles the myths, ideologies, and pathologies of the modern female body. Bordo explores our tortured fascination with food, hunger, desire, and control, and its effects on women's lives
Keywords: 2000-2009; 2000-2029; corps; discipline; fem1000; image corporelle; occident; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; études culturelles

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis